THE EFFECT OF TALENT MANAGEMENT AND WORKLOAD ON EMPLOYEE JOB SATISFACTION - Alfaruqhi, Muhammad; Zulhaida, Zulhaida; Indrayani, Henni; Identiti, Identiti; Lahamid, Qomariah (Economic and Science Faculty of Islamic State University, 2023)
Talent management is very important for organizations to be able to find the right people to carry out their work so that organizational performance will increase. Workload is one of the factors that will affect the performance of employees and organizations. This study aimed to determine the effect of talent management and workload on the job satisfaction of employees of the Regional Office of the Directorate General of Treasury, Ministry of Finance, Riau Province, either partially or simultaneously. Respondents in this study amounted to 40 people using the saturated sampling method (census). The data used are primary data and secondary data. The sampling technique in this study used a nonprobability sampling approach with saturated / census sampling techniques. The data analysis method used is a quantitative descriptive analysis with multiple linear regression. The results of the study show that talent management partially affects employee job satisfaction, as well as workload partially also affects employee job satisfaction Simultaneously talent management and workload influence the job satisfaction of employees of the Regional Office of the Directorate General of Treasury, Ministry of Finance, Riau Province. The magnitude of the effect is 67.1% while the remaining (32.9%) is influenced by other variables not examined in this study.